The Global Health Cost of PM2.5 Air Pollution : A Case for Action Beyond 2021 - World Bank (Washington, DC: World Bank, 2021)
According to the Global Burden of Disease 2019 study, air pollution from fine particulate matter caused 6.4 million premature deaths and 93 billion days lived with illness in 2019. Over the past decade, the toll of ambient air pollution has continued to rise. Air pollution’s significant health, social, and economic effects compel the World Bank to support client countries in addressing air pollution as a core development challenge. This publication estimates that the global cost of health damages associated with exposure to air pollution is $8.1 trillion, equivalent to 6.1 percent of global GDP. People in low- and middle-income countries are most affected by mortality and morbidity from air pollution. The death rate associated with air pollution is significantly higher in low-and lower-middle income countries than in high-income countries. This publication further develops the evidence base for air-quality management through up-to-date estimates of air pollution’s global economic costs. The analyses presented here build on previous cost estimates by the Bank and its partners, as well as on more comprehensive air-quality data from monitoring stations in many cities across the world. By providing monetary estimates of air pollution’s health damages, this publication aims to support policy makers and decision-makers in client countries in prioritizing air pollution amid competing development challenges. Its findings build a robust economic case to invest scarce budgetary resources in the design and implementation of policies and interventions for improving air quality. Such investments will deliver benefits for societies at large, and particularly for vulnerable groups. This publication builds a strong case for scaling up investments for air pollution control in low-and middle-income countries.